P12 A novel model of cardiomyopathy reveals a tissue specific role for the complex i assembly factor ecsit. (21st March 2018) - Nicol, T; Falcone, S; Blease, A; Scudamore, C; Hirst, J; Viscomi, C; Zeviani, M; Brown, SDM; Potter, PK
Abstract : Here we present a mouse model with a missense mutation in the gene Ecsit that shows a progressive cardiomyopathy from 4 weeks of age with no other overt phenotypes. ECSIT is known to play a role in development and immune signalling but is also thought to function as an assembly factor of complex I. Western blot analysis of tissue lysates revealed a significant reduction in complex I proteins in heart tissue, whereas all other complexes were unaffected. In addition, Seahorse analysis of isolated mitochondria shows a significant reduction in the respiration rates of cardiac mitochondria, whilst no differences could be seen in mitochondria isolated from brain tissue. In-gel activity demonstrated a significant drop in complex I activity of cardiac mitochondria, whilst brain mitochondria are maintained at close to normal levels. Blue native PAGE performed on cardiac mitochondria shows that this mutation affects ECSIT's role in a limited number of complex I sub-assemblies. However, this is unique to the heart and mitochondria from brain tissue show no changes in any of the same sub-assemblies, supporting the initial findings that there is normal complex I assembly in the brain. A potential mechanism lies in the discovery of a previously undescribed 16 kDa fragment of ECSIT that is present in WT cardiac mitochondria but not in mutant. This fragment is also undetectable in mitochondria isolated from brain tissue, indicating a tissue specific cleavage of ECSIT protein as a method of action.